Patient perspectives on multidimensional learning and person-centred care: interviews with persons living with type 2 diabetes - Alma Dautovic; Eva Brink; Susanne Andersson; Ulla Fredriksson-Larsson (Scandinavian Journal of Primary Health Care)
Objective The objective of this study was to explore patients’ learning and support needs within contemporary diabetes care to help them deal with daily life challenges.Design A qualitative descriptive design was used following the Consolidated Criteria for Reporting Qualitative Studies. The 15 individual face-to-face interviews were analysed using qualitative content analysis.Setting Participants were drawn from three healthcare centres in rural and urban regions of West Sweden.Participants The study involved 15 patients (8 men, 7 women) with T2DM who experienced contemporary diabetes care.Results Patients expressed a strong desire for access to person-centred, multidimensional learning, with a focus on genuine partnership, tailored education, and emotional engagement. Digital tools were seen as valuable aids in their self-care efforts. Sub-themes were ‘Desiring genuine partnership and tailored patient education’ and ‘Needing support related to altered perspectives on life and awareness of care standards but with finite care resources’.Conclusion The findings suggest that integrating person-centred, multidimensional learning strategies into diabetes care could be beneficial, particularly when addressing both practical and emotional needs. Encouraging active patient engagement through flexible digital solutions and providing support for emotional well-being may improve the overall patient experience. However, further research and practical application are needed to fully understand how these strategies could be effectively implemented to support patients with T2DM in managing their daily health challenges.